Surat Keterangan Notaris Dalam Konteks Labeling Cover Note - Karma Resen, Made Gde Subha (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
The purpose of this writing is to find out the substance that can be applied to a Notary’s statement and the reason for a Notary’s statement being labeled as a cover note. This study uses normative research methods with the problem of voidness in norms with statutory, conceptual, and analytical approaches. The sources of legal materials used consist of primary legal materials that come from laws and regulations related to legal issues, secondary legal materials obtained from journals, expert views and the results of previous research as well as tertiary legal materials obtained from legal dictionaries and language dictionaries which are described qualitatively. The results of the research show that the substance that can be applied to a Notary’s statement is a statement that explains the facts about events that actually happened and not as a guarantee for something. A notary statement with cover note label is a term used in practice that has been going on continuously. The cover note labeling describes the condition of the notary's statement containing the substance of protecting, guaranteeing and promising. This substance has the potential to cause legal problems for notaries and consequences for civil law liability, administrative law, and criminal law. Tujuan penulisan ini yaitu untuk mengetahui substansi yang dapat diterapkan pada surat keterangan notaris dan penyebab surat keterangan notaris yang dilabeling Cover Note menimbulkan permasalahan hukum. Penelitian ini menggunakan metode penelitian normatif dengan adanya permasalahan kekosongan norma dengan jenis pendekatan perundang-undangan, konseptual dan pendekatan analisis. Sumber bahan hukum yang digunakan terdiri dari bahan hukum primer yakni peraturan perundang-undangan yang berkaitan dengan isu hukum, bahan hukum sekunder yang didapatkan dari jurnal, pandangan ahli maupun hasil penelitian terdahulu dan bahan hukum tersier dididapatkan dari kamus hukum maupun kamus bahasa yang diuraikan secara kualitatif. Hasil penelitian menunjukkan bahwa substansi yang dapat diterapkan pada surat keterangan adalah pernyataan yang menerangkan fakta terhadap peristiwa yang benar terjadi menyangkut kewajiban dan kewenangannya, serta bukan sebagai jaminan/penanggungan terhadap sesuatu. Surat keterangan notaris yang dilabeling covernote merupakan istilah dalam praktek yang telah berlangsung terus menerus.  Labeling covernote tersebut menggambarkan keadaan surat keterangan notaris mengandung substansi melindungi, menjamin dan menjanjikan. Substansi ini berpotensi menimbulkan permasalahan hukum bagi notaris dan berkonsekuensi pertanggungjawaban perdata, administratif, dan pidana.